ΔV1‐1 Reduces Pulmonary Ischemia Reperfusion‐Induced Lung Injury by Inhibiting Necrosis and Mitochondrial Localization of PKCδ and p53. Issue 1 (14th September 2015) - Kim, H.; Zhao, J.; Zhang, Q.; Wang, Y.; Lee, D.; Bai, X.; Turrell, L.; Chen, M.; Gao, W.; Keshavjee, S.; Liu, M.
Abstract : Ischemia–reperfusion (IR)‐induced lung injury is one of the major contributing factors of morbidity and mortality after lung transplantation. To determine the IR‐induced molecular changes in lung epithelial cells, we developed a cell‐culture model that simulates lung preservation and transplantation. Six hours of cold ischemic time (CIT) and reperfusion elicited production of multiple inflammatory cytokines and chemokines and increased expression of endoplasmic reticulum (ER) proteins. Prolonged hypothermic condition (18 h CIT) reduced ER stress protein levels, and induced apoptosis and necrosis (via mechanisms related to mitochondrial permeability transition pore opening). Protein kinase C (PKCδ) was activated during CIT, and its downregulation via small interference (si) (in siRNA) RNA reduced IR‐induced cytokine production and apoptotic cell death. δV1‐1, a PKCδ peptide inhibitor, reduced translocation of PKCδ and p53 to the mitochondria after 18 h CIT, rescued ER stress protein expression, and converted the major mode of cell death from necrosis to apoptosis. Administration of δV1‐1 effectively reduced lung transplantation and IR‐induced pulmonary injury in rats. Therefore, inhibition of PKCδ by δV1‐1 could be an effective strategy to ameliorate IR‐induced lung injury by inhibiting the signaling pathways leading to necrosis. Abstract : Protein kinase C δ inhibition by δV1–1 inhibits ischemia‐reperfusion—induced infl ammation and necrotic cell death after lung transplantation by preventing mitochondrial translocation of protein kinase C δ and p53.